Combined duodenal and jejunal atresia forming a bile filled cyst, presenting as an abdominal mass: A case report and review of the literature - Ahmad Zaghal; Timothy M. Bahr; Graeme J. Pitcher (Elsevier, 2015)
The simultaneous occurrence of duodenal and jejunoileal atresia in the newborn is very rare. This is not surprising considering the unrelated embryogenesis behind the development of the two congenital anomalies. We present a case of duodenal atresia associated with an apple peel jejunoileal atresia in a newborn presenting with a prenatal diagnosis of an abdominal cystic mass and a palpable abdominal mass at birth. Exploration revealed a type 3 duodenal atresia followed by a type 3b proximal jejunal atresia (apple peel configuration), with a dilated short segment of bowel between the two. This segment of bowel was the cystic structure detected prenatally and preoperatively on exam. Double foregut atresias should be considered in the differential diagnosis of right upper quadrant cystic masses in the newborn period.